#MeToo : unveiling abuse - Borgert-Spaniol, Megan, 1989- (#Movements., 2020)
Outlines the history and development of the #MeToo movement for young readers. Recounts the history of sexual assault and harassment, the activists and victims who've fought for justice, and the demonstrations and organizations that formed as a result. Photographs, a timeline of important events, and a QR code that links to further reading augment the text.